Analisis Uses and Gratifications Mahasiswa dalam Mencari Sumber Pembelajaran di Media Sosial - Dwinta Herliana Patricia Pattiselanno; Aryo Pinandito; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Every social media user certainly has certain motives in meeting their needs and satisfaction through social media. This is in accordance with the Uses and Gratifications (U&G) theory, where a media cannot influence the media or content one chooses, including as a support for learning. This study aims to analyze the behavior of students at the Faculty of Computer Science, University of Brawijaya regarding student behavior when using social media to find learning resources. This study uses a qualitative-descriptive method in order to understand other people's understanding of a phenomenon. The collection of data in this study was by means of semi-structured interviews, then the data were analyzed using thematic analysis. The results of this study indicate that students have various ways of obtaining and using learning information obtained on social media. In addition, students look for learning resources on certain social media for various reasons such as many users, easy access, and others. Each student also has preferences for the type of learning content they are looking for. Factors underlying student satisfaction with learning resources obtained through social media are influenced in terms of content, information obtained, and the use of social media.